PEMBERIAN STRETCHING ABDOMINAL DAN REFLEXOLOGY TERHADAP NYERI DISMENORE PRIMER PADA ANAK SMA PEMBANGUNAN NASIONAL PAGAR MERBAU - Tati Murni Karokaro; Miftahul Zannah; Nurhapni Pulungan (JURNAL PENGMAS KESTRA (JPK), 2021)
Primary dysmenorrhea is pain during menstruation without any abnormalities in the genital organs, pain is felt before or on the first day of menstruation and lasts for several hours. To find out the effect of giving stretching abdominal and reflexology on primary dysmenorrhea pain in Senior high school students of SMA Pembangunan Nasional Pagar Merbau 2021. Research design is quasi-experiment. The population in this study were students of class XI SMA Pembangunan Nasional in Pagar Merbau. From January to June there were 30 students. Data were analyzed using the Wilcoxon test. The results obtained are the mean before intervention 2.86 and the mean after intervention 1.12, while the standard deviation after intervention 0.145. The results of the Wilcoxon statistical test with sig (2-tailed) p = 0.000 which means ≤ 0.05, which means that there is an effect of abdominal stretching and reflexology on the level of primary dysmenorrhea pain in high school teenage students. Stretching abdominal and reflexology given before menstruation twice a week for 3 weeks. There is a significant effect on the level of primary dysmenorrhea pain in grade XI students at SMA Pembangunan Nasional Pagar Merbau. Therefore, it is desirable for those who experience primary dysmenorrhea during menstruation to undertake non-pharmacological treatment which has been proven to reduce menstrual pain.